1996
DOI: 10.1007/s004200050062
|View full text |Cite
|
Sign up to set email alerts
|

An updated cohort mortality study of workers at a northeastern United States petroleum refinery

Abstract: An update of a cohort study of 4855 employees at a Paulsboro, New Jersey refinery was conducted to further examine mortality patterns. The earlier study investigated refinery workers employed for a minimum of 1 year between 1 January 1946 and 1 January 1979. The vital status of these workers was ascertained through 1979. The update extended enrollment in the study and vital status follow-up for an additional 8 years (1980-1987). As in the previous study, mortality from all causes [standardized mortality ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…A collaborative animal experimental study also demonstrated a wide range of lesions in the nephrons of animals exposed to hydrocarbons compared to the controls. Most of these lesions were similar to those observed in humans and included immunoglobulin A (IgA) nephritis [91], mesengial nephropathy [118], crescentic nephropathy [119], focal gasoline constituents is associated with increased risk of renal function impairment, due to their potential to either initiate kidney injury or worsen extant impaired renal function, or both [95,96]. In many cases, the glomerular cells and tubular cells of the kidney are the most vulnerable site for injury [97].…”
Section: Nephrotoxicitymentioning
confidence: 64%
“…A collaborative animal experimental study also demonstrated a wide range of lesions in the nephrons of animals exposed to hydrocarbons compared to the controls. Most of these lesions were similar to those observed in humans and included immunoglobulin A (IgA) nephritis [91], mesengial nephropathy [118], crescentic nephropathy [119], focal gasoline constituents is associated with increased risk of renal function impairment, due to their potential to either initiate kidney injury or worsen extant impaired renal function, or both [95,96]. In many cases, the glomerular cells and tubular cells of the kidney are the most vulnerable site for injury [97].…”
Section: Nephrotoxicitymentioning
confidence: 64%
“…A recently completed study of workers at the Mobil Torrance refinery [Milcarek et al, 1994] reported an SMR of 120 (4 observed vs 3.3 expected, 95%CI ϭ 33-307). A study at the Mobil Paulsboro refinery [Collingwood et al, 1996] reported no significant increase of NHL (15 observed vs. 11.4 expected,…”
mentioning
confidence: 83%
“…These results are consistent with those from other refinery studies. In a recent review and meta-analysis of refinery studies, Raabe and Wong [1996] reported no increase in CML, ALL or CLL among refinery workers.…”
mentioning
confidence: 96%
“…Infante (10) referred to three studies conducted in gasoline-exposed workers: one showed strong associations between gasoline exposure, leukemia, and multiple myeloma; the second suggested a slight association with leukemia, but did not analyze data for multiple myeloma; and the third was inconclusive due to problems linked with study design. In 1996 Collingwood et al (16) reported that in a cohort study of (3). After gasoline application to skin, a decrease in glutathione concentration, glutathione S-transferase activity, and lipid peroxidation was observed in liver and brain (18).…”
Section: Human and Epidemiological Studiesmentioning
confidence: 99%